Investigating the Synergy of Integrated Project Delivery and Building Information Modeling in the Conservation of the Architectural Heritage - BRAHMI BANI FERIEL; KITOUNI ILHAM; SASSI BOUDEMAGH SOUAD (Journal of Contemporary Urban Affairs, 2018)
Architectural heritage conservation projects are one of the most risky and complex projects in the construction industry. Many studies have reported frequent performance failures in terms of time, cost and quality. To implement quality management in the conservation projects and enhance their performance; we propose the adoption of two emerging and innovative approaches: Integrated Project Delivery (IPD) and Building Information Modeling (BIM). Through an analysis of literature review (journals, white papers, norms and standards) on the subject, a comprehensive qualitative study in theoretical term has been carried out to define the potential advantages of the synergy between the BIM and IPD to face conservation issues and constraints through project lifecycle. Finally, we draw some general conclusions, summarize the implications for practice and set out recommendations for further research.